An extended interior-point method for transmit beamforming in multi-group multicasting - Bornhorst, N.; Davarmanesh, P.; Pesavento, M. (2012 Proceedings of the 20th European Signal Processing Conference (EUSIPCO), 2012)
We address the problem of transmit beamforming to multiple cochannel multicast groups where the total transmitted power is minimized subject to quality-of-service (QoS) constraints at the receivers. The iterative second-order cone programming (SOCP) approach recently proposed in [2] is a powerful tool to solve this problem and has certain advantages over other state-of-the-art techniques like the semidefinite relaxation (SDR) approach. However, we show in this paper that its computational complexity is unnecessarily high. Therefore, we propose to eliminate the superfluous part of its computational effort by combining the concept of the iterative SOCP method with that of interior-point methods. Computer simulations show that by this means, we can substantially reduce the computational complexity of the iterative SOCP method while preserving its good performance.